Helicobacter pylori infection is high in paediatric nonulcer dyspepsia but not associated with specific gastrointestinal symptoms - Correa Silva, Rgs [UNESP]; MacHado, Nc [UNESP]; Carvalho, Ma [UNESP]; Rodrigues, Mam [UNESP] (Wiley, 2016)
Aim The association between Helicobacter pylori infection and gastrointestinal symptoms is debatable in childhood. We examined the potential relationship between H. pylori infection and gastrointestinal symptoms in Brazilian children with nonulcer dyspepsia. Methods This prospective observational study analysed 240 Brazilian children and adolescents (68.7% girls) with chronic nonulcer dyspepsia, who underwent upper gastrointestinal endoscopy and biopsy. Their mean age was 9.8 years (range 4-17). Upper gastrointestinal symptoms, including abdominal pain, nausea, burning, early satiety, belching and weigh loss, were evaluated by a questionnaire and H. pylori infection was determined by histopathology of gastric biopsies. Results H. pylori infection was identified in 123/240 patients (52%). There was no significant association between the H. pylori infection and gastrointestinal symptoms and no relationship between the infection and abdominal pain or pain characteristics. However, nausea was significantly associated with the H. pylori infection, with an odds ratio of 1.76 and 95% confidence interval of 1.1-2.94 p < 0.03. Symptoms lasting longer than 12 months were significantly more frequent in children with pangastritis than in those with antral gastritis (p < 0.05). Conclusion The prevalence of H. pylori infection was high in Brazilian children with nonulcer dyspepsia, but was not associated with specific signs and symptoms, except for nausea.
Keywords: Abdominal pain; Children; Gastrointestinal symptoms; Helicobacter pylori